An Analysis of Synergy Effect from Acquisition in PT Hakaaston and Its Subsidiary - Ayu Hutami Hariyanti (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – PT. Hakaaston has acquired three subsidiaries, namely PT. Bhirawa Steel, PT. Semen Indogreen Sentosa and PT. Catur Armindo Putra, which began in 2019. The acquisitions are generally expected to bring benefits to the acquiring company. However, after three years of implementing the acquisition, there has been no significant change, raising the question of whether the conducted acquisition that had been carried out was based on the right strategy and careful considerations. Aim – This study aims to obtain the evidence regarding the effects of the acquisition conducted by PT. Hakaaston. Design / Methodology / Approach – Researchers conducted an in-depth analysis of the condition using a mixed method approach to determine whether the acquisition that has been carried out could lead to financial synergies or operational synergies. The research process divided into several steps, the first step involved quantitative research, where the researcher conducted the statistical tests on the ratio of the company's financial reports of 2019-2022 which continued into the next step which involved qualitative in the form of in-depth analysis through interviews with informants. The results of statistical tests and interviews are integrated to allow the researcher to conclude whether synergy has been achieved from the acquisition. Findings – The empirical findings based on post-acquisition financial statement report found that 2 out of 3 subsidiary companies experienced financial improvements while the holding company, as the acquirer, experienced a decline subsequent to the company’s acquisition. The result of the analysis interview with the informants explained that the conducted acquisition focus is not only on financial synergies but also on operational synergies in which the company played a role in supporting the construction of the Trans Sumatra Toll Road. Conclusion - The initial quantitative analysis found that there is no significant financial or operational synergy among the subsidiary companies of PT. Hakaaston, meanwhile the qualitative analysis found that in terms of operational synergy, according to the informants from both the subsidiary companies and the holding company, operational synergy has been achieved. Research implication – The findings of this study can serve as the basis for further research on Mergers & Acquisitions (M&A) policies which are not only beneficial for one party but more towards economic benefits. In addition, the research results can be used as a consideration in making decisions regarding future Mergers & Acquisitions (M&A) plans for companies to make them more effective. Research Limitations – The limitation of this study is the relatively small-time frame of the research process, as the acquisition only took place in 2019. Therefore, future research can consider using a longer time frame to examine the post-acquisition period.